(untitled) (Journal of Analytical Oncology, 2013)
We report on two patients, successfully treated by the combination therapy of gemcitabine and 24-h intravenous infusion of cisplatin, who were initially diagnosed with node-positive advanced urothelial cancer. Each patient had a very good clinical response and underwent curative radical surgery after gemcitabine/cisplatin chemotherapy. A microscopically detailed examination of surgically obtained specimens showed the complete disappearance of malignant cells in the two cases. As a pilot study, we have used the regimen of gemcitabine plus 24-h continuous infusion of cisplatin, instead of bolus injection, for the treatment of 20 patients with node-positive or metastatic urothelial cancer. The clinical response rate in this regimen was 75% (complete response 7/20; 35%, partial response 8/20; 40%). The median overall survival was 665 days. As for the adverse effects, the incidences of severe neutropenia and thrombocytopenia (grade 3-4) were 20% and 15%, which might be less toxic than conventional gemcitabine plus cisplatin therapy. The 24-h infusion of cisplatin combined with gemcitabine can be highly recommended as neoadjuvant chemotherapy for locally advanced urothelial cancer.